Modeling study of silica membrane performance for hydrogen separation. Issue 5 (23rd July 2015) - Aghaeinejad‐Meybodi, Abbas; Ghasemzadeh, Kamran; Babaluo, Ali Akbar; Morrone, Pietropaolo; Basile, Angelo
Abstract The main aim of this work is the presentation of quantitative analysis of silica membrane for hydrogen separation from methanol steam reforming products to produce high purity hydrogen. This study uses a single stage silica membrane in three different flow patterns, namely cocurrent, countercurrent and cross flow, for separation of a typical methanol steam reforming products stream. The modeling results showed that the silica membrane presents noticeable performance to produce high purity hydrogen. In particular, by considering the stage cut, it was found that the hydrogen molar fraction in the permeate side was decreased by increasing the stage cut from 0.1 to 0.65, whereas the carbon monoxide molar fraction increased for all of the flow patterns. In addition, a similar effect was observed for membrane surface area. Moreover, the retentate side pressure effect was positive on the silica membrane performance, although the improvement of silica membrane performance was not considerable for more than a pressure gradient of 3 bar. This analysis indicated that by using single stage silica membrane, 99% hydrogen molar fraction and 0.4% carbon monoxide molar fraction in the permeate side can be achieved for a pressure gradient equal to 3 bar. © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.